Classificação anatômica da região anterior do terceiro ventrículo em pacientes submetidos à neurocirurgia endoscópica - REIS, Rafaela D’Angelo dos (2019)
Currentmedicinehasusedscientificadvancesenablingtheuseofmedicalequipment thataccessthehumanbodywiththeleastinvasioninsurgicalprocedures.Anexample ofthisisendoscopicneurosurgery.Endoscopicstudieshaveaidedintheinvestigation of the lateral ventricles and third ventricle, and such imaging knowledgecomplements the traditional anatomy. The advantages of using the endoscope, as well as the diseasetobetreated,allowtheventricularstudy anatomical studywithpossibilityoflight control and its intensity, with registration in photos and video recordings. In addition,it is a minimally invasive procedure with ease of handling. This study aims to study the endoscopic anatomy of the third ventricle using endoscopic techniques in patients operated on at the the Hospital of Clinics of the Federal University of the Triângulo Mineiro. The methodology used was the analysis of intraoperative videos and images of 50 patients submitted to the endoscopic thirdventriculostomy (TVE), from 2010 to 2017. The selection of patients was performed firstly by Neurosurgery records, complemented by medical records doctors. Thirty-six patients who met our criteria were selected for the study. Images of anatomical variations were organized in the following categories with respective results: Group 1 - Delicate floor (17%), Group 2 - Thick floor (25%), Group 3 - Partially erased floor (14%), Group 4 - Balloon floor3%),Group 6 - Third narrow ventricle (3%), Group 7 - Elevated floor (8%), Group 8 - Dislocated mammillary bodies (3%), 10 - Thickening prior to mammillary bodies (0%). The most present change was the thickened floor. Since some anomalies do not interfere directly in the TVE, but others can compromise the success of the operation, being reported some cases of abandonment of the surgery.